Sosialisasi Anti-Bullying Sebagai Upaya Pencegahan Perundungan di Kalangan Siswa Sekolah Dasar: Program Kerja Kuliah Kerja Nyata (KKN) Universitas Riau di Desa Sotol - Nayla Nanda Friadi; Aulia Rahma Putri; Muhammad Fauzy; Aysha Safira Dosant; Zahwa Alyana Reksani; Natasya Ramadani; Ivanka Juliana; At Thahirah Syawali Ismi; Muhammad Habibi; Intika Audy Finansia; Erwin E (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Bullying in elementary schools is a social issue that significantly impacts children's psychological, social, and academic development. This article aims to describe the implementation and outcomes of the Anti-Bullying Awareness program conducted by University of Riau Community Service (KKN) students at SDN 003 Sotol (Sotol State Elementary School 003) in Sotol Village, Langgam District, Pelalawan Regency, Riau Province; this initiative was one of the group's priority projects. The activity took place on Wednesday, July 15, 2026, at 07:30 WIB, targeting students, teachers, and the school community. The implementation method involved an interactive presentation using visual aids, followed by a discussion and Q&A session. The material covered the definition and types of bullying, examples of bullying behavior, the impact on victims, appropriate actions to take when experiencing or witnessing bullying, the role of teachers in prevention, and how to be a good friend. The results demonstrated increased participant understanding and awareness regarding the dangers of bullying, the fostering of mutual respect among students, and the establishment of a collective commitment to creating a safe, comfortable, and bullying-free school environment. This program is expected to serve as a starting point for cultivating a child-friendly school culture that supports sustainable bullying prevention.